The cult of personality : how personality tests are leading us to mislabel our children, mismanage our companies, and misunderstand ourselves - Paul, Annie Murphy (New York : Free Press, 2004)
This book tells the surprising and disturbing story of the tests that claim to capture human nature. It goes behind the scenes to discover how personality tests are used in America's companies, its courts, its schools, and in organizations from churches to community centers to dating services. It exposes the serious flaws of personality tests, explaining why their results are often invalid, unreliable, and unfair.
Introduction -- 1. A most typical American -- 2. Rorschach's dream -- 3. Minnesota normals -- 4. Deep diving -- 5. First love -- 6.0 Child's play -- 7.0 The stranger -- 8.0 Uncharted waters -- Epilogue -- Acknowledgments -- Notes -- Index -- About the author.
Includes bibliographical references (p. [229]-291) and index.
Keywords: Personality tests -- United States; Personality tests for children -- United States; Employees -- Psychological testing -- United States; Personality tests -- Child -- United States; Psychology, Industrial -- United States